Perceptual deterrence research: Some additional evidence for designing studies - Demers, David K. (Journal of quantitative criminology, 1987)
Recently, serious questions have been raised about the validity of cross-sectional (“one-wave”) assessments of perceptual deterrence. Panel (“multiwave”) designs have, therefore, become the preferred method of conducting perceptual deterrence research. We question whether panel designs are always necessary. Our goal is to encourage renewed examination of cross-sectional designs. The primary method of accomplishing this goal is replication and extension of an earlier one-wave study. Following a review of the design issue, the paper continues with a brief description of the study to be replicated and extended. Presented next are the replication methods and findings. The paper ends with a discussion of the contours of an agenda for future research.